Comparison of early risk factors between healthy siblings and subjects with schizophrenia and bipolar disorder - Nunes, Rosany Guterrez; Carrilho, Carolina Gomes; Alves, Gilberto Sousa; Malaspina, Dolores; Kahn, Jeffrey Paul; Nardi, Antonio Egidio; Veras, André Barciela (Frontiers in Psychiatry, 2024)
The following work aims to compare the types and magnitude of risk events in patients with Schizophrenia and Bipolar Disorder and each of those groups with of a group of healthy siblings, exploring differences and similarities of the two psychotic disorders. Methods: Retrospective interviews were conducted with 20 families to investigate maternal and obstetric health, social support and the presence of early trauma for the affected family members and healthy siblings. Mothers were interviewed with the Prenatal Psychosocial Profile and each family participant was assessed with the Early Trauma Inventory, Screening Questionnaire of the Genomic Psychiatry Cohort and the Diagnostic Interview for Psychosis and Affective Disorders.Results: Obstetric and gestational history, pregnancy weight changes and early trauma were associated with offspring's mental illness, including statistically significant findings for complications of pregnancy, pregnancy weight changes, general trauma, physical punishment and emotional abuse. Conclusion: These findings highlight the different risk factor exposures that occur within a family, which may increase the risk for severe mental illness.